EMPOWERMENT OF WOMEN THROUGH SEWING SKILLS TRAINING FOR INCREASING INDEPENDENCE AND INCOME INDEWANTARA NORTH ACEH DISTRICT - Rahmaniar; Khairawati; Erna Isfayani; Fuadi; Wahyuddin (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2022)
The purpose of this community service activity is to provide additional knowledge for the community, especially groups of mothers who have free time, the potential to be independent with a home business but do not yet have the skills. To overcome this problem, the Community Empowerment Service program empowers women to increase their independence through sewing training. The target of this Community Empowerment Service activity is mothers and young women in the study group and this sewing training is held at the meunasah or Gampong meeting buildingPaloh Igeuh Village, Dewantara District, North Aceh Regency.The method of this service is socialization, training, and sewing assistance which includes: (1) Training on pattern making, cutting, and sewing on syar'i clothes, (2) training in the form of a brief explanation of the calculation of the profit obtained if it is from the production of syar'i clothes, (3) Sharia Entrepreneurship (4) Social Media Training in terms of promotion of syar'i clothing and (5) Economic benefits derived from independence, family income and blessings as well as basic introduction and materials needed to sew syar'i clothing. This community service partnership activity is carried out face-to-face or offline while adhering to health protocols. The results of the implementation of this activity are expected to be womenPaloh Igeuh Village, Dewantara District, North Aceh Regency.have understanding and knowledge in sewing, especially syar'i clothes and able to increase women's income and independencePaloh Igeuh Village, Dewantara District, North Aceh Regency.